Do Banks Hedge Using Interest Rate Swaps? - McPhail, Lihong Lu,Schnabl, Philipp,Tuckman, Bruce (National Bureau of Economic Research, 2023)
We ask whether banks use interest rate swaps to hedge the interest rate risk of their assets, primarily loans and securities. To this end, we use regulatory data on individual swap positions for the largest 250 U.S. banks. We find that the average bank has a large notional amount of swaps– 434 billion, or more than 10 times assets. But after accounting for the significant extent to which swap positions offset each other, the average bank has essentially no net interest rate risk from swaps: a 100-basis-point increase in rates increases the value of its swaps by 0.1% of equity. There is variation across banks, with some bank swap positions decreasing and some increasing with rates, but aggregating swap positions at the level of the banking system reveals that most swap exposures are offsetting. Therefore, as a description of prevailing practice, we conclude that swap positions are not economically significant in hedging the interest rate risk of bank assets
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Bank; Zinsderivat; Zinsrisiko; Hedging; Swap; USA; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Financing Policy; Financial Risk and Risk Management; Capital and Ownership Structure; Value of Firms; Goodwill